Acute Atherosis of the Uterine Spiral Arteries: Clinicopathologic Implications - Joo-Yeon Kim; Yeon Mee Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Acute atherosis is unique vascular changes of the placenta associated with poor placentation. It is characterized by subendothelial lipid-filled foam cells, fibrinoid necrosis of the arterial wall, perivascular lymphocytic infiltration, and it is histologically similar to early-stage atherosclerosis. Acute atherosis is rare in normal pregnancies, but is frequently observed in non- transformed spiral arteries in abnormal pregnancies, such as preeclampsia, small for gestational age (SGA), fetal death, spontaneous preterm labor and preterm premature rupture of membranes. In preeclampsia, spiral arteries fail to develop physiologic transformation and retain thick walls and a narrow lumen. Failure of physiologic transformation of spiral arteries is believed to be the main cause of uteroplacental ischemia, which can lead to the production of anti-angiogenic factors and induce endothelial dysfunction and eventually predispose the pregnancy to preeclampsia. Acute atherosis is more frequently observed in the spiral arteries of the decidua of the placenta (parietalis or basalis) than in the decidual or myometrial segments of the placental bed. The presence and deeper location of acute atherosis is associated with poorer pregnancy outcomes, more severe disease, earlier onset of preeclampsia, and a greater frequency of SGA neonates in patients with preeclampsia. Moreover, the idea that the presence of acute atherosis in the placenta may increase the risk of future cardiovascular disease in women with a history of preeclampsia is of growing concern. Therefore, placental examination is crucial for retrospective investigation of pregnancy complications and outcomes, and accurate placental pathology based on universal diagnostic criteria in patients with abnormal pregnancies is essential for clinicopathologic correlation.